Keliling kampus dunia : Petualangan dua mahasiswa ITB / Erlangga Ibrahim & Fadel Muhammad ; editor A-Ariobimo Nusantara - IBRAHIM, Erlangga; Muhammad, Fadel; Nusantara, A. Ariobimo (2009)
xii,198 hlm. ilus. 23 cm